2017
DOI: 10.7150/ijms.17545
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Effects of Sugammadex in combination with Rocuronium or Vecuronium

Abstract: Rocuronium (ROC) and Vecuronium (VEC) are the most currently used steroidal non-depolarizing neuromuscular blocking (MNB) agents. Sugammadex (SUG) rapidly reverses steroidal NMB agents after anaesthesia. The present study was conducted in order to evaluate neuronal effects of SUG alone and in combination with both ROC and VEC. Using MTT, CASP-3 activity and Western-blot we determined the toxicity of SUG, ROC or VEC in neurons in primary culture. SUG induces apoptosis/necrosis in neurons in primary culture and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…although it is thought to increase in situations such as trauma, it is not possible to transfer sugammadex to cerebral cells as intensely as in this study. Cerebral cell cultures were kept in vitro with sugammadex solution and apoptosis was examined by Aldasoro et al 23 In this study, no statistically significant difference has been observed between the groups receiving sugammadex and the group receiving mannitol after trauma in terms of neuronal density. Furthermore, NeuN and activated CASP3 positive cells were low.…”
Section: Discussionmentioning
confidence: 69%
“…although it is thought to increase in situations such as trauma, it is not possible to transfer sugammadex to cerebral cells as intensely as in this study. Cerebral cell cultures were kept in vitro with sugammadex solution and apoptosis was examined by Aldasoro et al 23 In this study, no statistically significant difference has been observed between the groups receiving sugammadex and the group receiving mannitol after trauma in terms of neuronal density. Furthermore, NeuN and activated CASP3 positive cells were low.…”
Section: Discussionmentioning
confidence: 69%
“…Reversal of neuromuscular blockage induced by steroidal neuromuscular blocking agents such as rocuronium can be achieved using normal dose of sugammadex. Intravenous sugammadex demonstrates linear pharmacokinetic properties over the dose range of 1-16 mg/kg [24] . Therefore, 16 mg/kg sugammadex were given to rats in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Research into Rb and Vb mainly refers to its effects on neurones (24)(25)(26), but wider effects have not been investigated in vitro. Thus, it is important to study the effect of muscle-relaxant anesthetics, especially Rb, Vb or CB, on tumor metastasis both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%